2022
DOI: 10.1007/s10875-021-01199-w
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Cell Transplantation for Inborn Errors of Immunity Other than Severe Combined Immunodeficiency in Japan: Retrospective Analysis for 1985–2016

Abstract: Hematopoietic cell transplantation (HCT) is a curative therapy for most patients with inborn errors of immunity (IEI). We conducted a nationwide study on HCT for patients with IEI other than severe combined immunode ciency (non-SCID) in Japan. MethodsData from the Japanese national database (Transplant Registry Uni ed Management Program, TRUMP) for 567 patients with non-SCID IEI, who underwent their rst HCT between 1985 and 2016, were retrospectively analyzed. ResultsThe 10-year overall survival (OS) and event… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…The 3-year OS rates in the current study were 73.0% for the NMD group and 73.4% for the MD group. These rates align with OS estimates from multicenter studies on HSCT and children with immunodeficiencies in Brazil [33], Colombia [34], and Japan [35]. For MD the OS appears to be higher compared to previous study conducted in Brazil [36] and to rates reported in other countries [37].…”
Section: Discussionsupporting
confidence: 82%
“…The 3-year OS rates in the current study were 73.0% for the NMD group and 73.4% for the MD group. These rates align with OS estimates from multicenter studies on HSCT and children with immunodeficiencies in Brazil [33], Colombia [34], and Japan [35]. For MD the OS appears to be higher compared to previous study conducted in Brazil [36] and to rates reported in other countries [37].…”
Section: Discussionsupporting
confidence: 82%
“…The OS in IEI after HSCT varies between countries; recent reports demonstrate lower rates of survival in low-income countries and higher rates in high-income countries. Thus, the reported OS is 0.61 in India [ 20 ], 0.63 in Colombia [ 21 ], 0.71 in Brazil [ 22 ], 0.67–0.74 in Japan, [ 23 , 24 ], 0.83 in the UK [ 8 ], and least 0.92 Germany [ 7 ]. In Russia, the OS in all IEI patients who received HSCT is 0.74, and since 2012, the OS has improved from 0.54 to 0.76.…”
Section: Discussionmentioning
confidence: 99%